PENGATURAN INDIKASI GEOGRAFIS TERHADAP PRODUK WINE SALAK BEBANDEM KARANGASEM - apriliani, kadek; Sudirga, Made; Putra, Putu Angga Pratama; Darsana, Kadek Damayani Indriamitha; Krisnadewi, Anak Agung Putri (Fakultas Hukum Universitas Ngurah Rai, 2024)
Geographical indication (GI) is a form of legal protection that gives products a distinctive identity based on their geographical origin. In Indonesia, GI has been applied to various products, including locally processed products such as Burdendem Karangasem salak wine. This article discusses the IG regulation of the Burdendem Karangasem salak wine product and its impact on the agricultural industry and local economy. Burdenem Karangasem salak wine is a unique product produced from salak fruit typical of the Karangasem area, Bali. IG provides protection for this geographical name, ensuring that only products originating from the area can use the label